RECENT RECORDS OF GLOBALLY ENDANGERED WHITE HEADED DUCK OXYURA LEUCOCEPHALA IN PAKISTAN - Z. Ali; S.S. Ahmad; M.N. Khan; M. Akhtar (Journal of Animal and Plant Sciences, 2007)
The records show that the number of White-headed Duck is reduced from over 1000 to only ten in the course of past 35 years. It indicates that their number may reach zero at any coming year, if the present alarming rate of decline was to continue. It is believed that the South Asian migratory flock of White-headed Duck winters only at Uchalli Wetlands Complex in Punjab, Pakistan. There are however, indications that these birds may go to other areas in Punjab or elsewhere due to recent drought and shrinkage in habitat at Uchalli Wetlands Complex. Historically recorded sites since 1883 therefore, have more potential to survey for search of White-headed Duck than any other sites. To investigate their true status on alternate winter grounds, an extensive survey was undertaken from 28th January to 21st February 2003. The survey encompassed areas were Rawal Lake, Kallar Kahar Lake, Shahpur (Jehlum Bridge), Jahlar Lake, Khabbaki Lake, Uchalli Lake, Nammal Lake, Rangpur Lake, Mianwali (Chashma Barrage), Kharal Lake, Khangarh Lake, Bahawalnagar (Sulmanki Headworks), Chalianwala, Hafizabad (Qadirabad Headworks), Sialkot (Marala Headworks), and Jassar (River Ravi). These wetlands are extensive enough to lure White-headed Duck. A total of 33 White-headed Ducks were recorded at four different sites viz.: 22 at Uchalli, two at Jahlar, two at Nammal and seven at Rawal lake. Khabbaki, Kharrar and Chalianwala sites faced a severe drought following scanty rainfall in the catchment area. The sex ratio (male/female) of past seventeen years was found to be 46:54. The results depict that the reason for decline is other than natural calamities and may be hunting at non wintering sites due to distinction in male plumage.
Keywords: White-headed Duck; Survey; Shannon-Weiner Biodiversity Index; Conservation.